Managing Diversity for Quality: Multicultural Education Management in a Plural Elementary School Context - Hartinah, Hartinah; Yuliana, Yuliana; Thamrin, Putri Aulia (Universitas Nurul Jadid, 2026)
This study investigates how multicultural education management is implemented to enhance the quality of learning in an elementary school characterized by ethnic and cultural diversity. Using a qualitative case study design, the research explores how planning, instructional practice, evaluation, and institutional reinforcement mechanisms operate within a plural educational setting. Data were collected through in-depth interviews, document analysis, and examination of routine managerial practices within the school. The findings indicate that multicultural education management is enacted through a structured cycle consisting of instructional planning, adaptive teaching strategies, periodic evaluation, and recognition systems such as academic awards and competition participation. Teachers play a pivotal role in translating institutional policies into inclusive classroom practices, while the principal ensures consistency through supervision and reflective evaluation forums. The study also identifies a differentiated impact pattern: students with strong learning absorption demonstrate academic advancement, whereas varied learning characteristics require ongoing pedagogical adjustment. These findings suggest that educational quality in multicultural contexts depends on the alignment between managerial coherence and instructional flexibility. The study contributes to a deeper understanding of how structured governance can sustain inclusive and quality-oriented education within culturally diverse school environments.